ACCOUNTING FOR OPTIONS AND ANALYSIS OF USE OF OPTION COMBINATION STRATEGIES - I. Derun (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article deals with problems of accounting for options in Ukraine, namely: value expression of initial cost of options, their revaluation, accounting of premiums, financial assets and financial liabilities and variation margin. The paper offers ways of solution of these problems which based on harmonization with IAS 32, IAS 39, IFRS 7 and IFRS 9. The study considers option combination strategies (straddle, strangle, strap, strip) and approaches of identification of possible financial results for investors which use these strategies. Examples of possible financial results are provided for buyers and sellers of options which use option combination strategies.